Shakespeare’s Eternal Voice: Fictional autobiographies of the Bard (Altre Modernità, 2017)
The paper focuses on two fictional works that strive to revive Shakespeare's voice, that is Christopher Rush's "Will" (2007), and J. P. Wearing's ÒThe Shakespeare's Diaries: A Fictional Autobiography" (2007), which although significantly different in terms of form find common ground in employing the first-person narrative in order to depict Shakespeare's life. The author analyses the image of the Bard that emerges from the novel and the diary, and the way in which both works transform the facts known from certain documents or based on extensive research into a fictional narrative. He argues that although both works try to satisfy the curiosity of the readers, they belong to two different types of representations found in fictional biographies of the Bard, and therefore the images they create address different kinds of collective desires and fantasies of the mass audience.
Keywords: Shakespeare; William; fictional autobiography; biography; biofictions; Rush; Christopher; Wearing J. P.